CHINA’S PRESENCE IN KAZAKHSTAN: MYTHS AND REALITY - SYROEZHKIN, Konstantin (CENTRAL ASIA AND THE CAUCASUS, 2011)
Evaluating the level of China’s presence in Kazakhstan and, most important, the attitude of the government and society toward this phenomenon is a thankless task, although both interesting and necessary from the viewpoint of national security. This evaluation is not only complicated by the numerous myths surrounding this topic, but also by the unavailability of some of the information, the reason for which is not entirely clear. And it is this “secrecy” that often gives rise to the myths about Kazakh Chinese relations, as well as the phobias about China itself. Information about major Kazakh Chinese projects is even harder to come by. It is entirely out of bounds, while the facts that reach the pages of the Kazakh and foreign press give rise to many questions, to put it mildly. This is particularly true regarding the details of project funding, the participation of the sides in the implementation and further operation of a project, its recoupment, its economic and geopolitical importance for Kazakhstan and China, and so on. What is there to hide? Openly publicizing a bilateral document is always better than rumors and conjectures about it. Government officials look very untrustworthy when they begin trying to find justification for what could have been said openly. The same goes for Chinese labor migration. There are more than enough myths and phobias surrounding this problem, but hardly any serious studies, although this absence can be explained. The official statistics provided by the internal affairs structures give no cause for concern, but a visit to any Kazakh market tells a different story. Albeit fragmentary, but very convincing statistics regarding the enterprises with Chinese investments registered by the judicial authorities also tell a different story. Any ordinary citizen who familiarizes himself with these statistics gets the impression that China is “marking out its territory,” and this conclusion is what feeds the “Chinese expansion” theory. The geopolitical arguments of some authors about China’s presence in Central Asia and Kazakhstan give rise to many questions. It is blatantly clear that China is fortifying its position in the Central Asian region and particularly in Kazakhstan, but this fact can in no way justify the conclusion that “China will begin its advance on the former Soviet Union from Kazakhstan.”1 Even more far-fetched is the conclusion other “experts” come to when analyzing the changing geopolitical situation in Central Asia and the active changes going on in Kazakhstan: “The main question today is where the demarcation line will fall when Russia and China divide up Kazakhstan.”2